FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA ANEMIA PADA IBU HAMIL DI PUSKESMAS COT IE JUE KECAMATAN PEUSANGAN KABUPATEN BIREUEN TAHUN 2023 - Sari, Nur Mala; Husna, Fadhlinal (Jurnal Inovasi Kesehatan Masyarakat, 2024)
Pregnancy-related anemia is a widespread issue because it has a significant impact on the quality of human resources and reflects the socioeconomic status of the community. Pregnant women's anemia is considered "potentially harmful to mother and child," thus it requires extra care. employees providing health services during the day (Manuaba, 2001). The purpose of this study was to identify risk factors for anemia prevalence in pregnant women at Cot Ie Jue Medical Center in the Peusangan District of the Bireuen Regency in 2023. The kind of study that was conducted This cross-sectional technique study is quantitative in nature. Pregnant women in their third trimester made up the study's population, and the 54 respondents who participated in the random sampling process served as the sample. Knowledge (p-value = 0.000 < 0.05), age (p-value = 0.000 < 0.05), equivalency level (p-value = 0.002 < 0.05), number of prenatal visits (p value = 0.001 < 0.05), and compliance with Fe tablets (p-value = 0.000 < 0.05) are related to anemia prevalence in pregnant women. These findings will aid in better monitoring and early detection of anemia risk factors, particularly in women of gestational age. expectant women with DEC should be identified early and receive prompt treatment, as should the mother's age, parity, and other factors.